Vitamin D Levels in Chronic Diseases in Primary Care - A.Sabic; Dz.Sabic; A.Zejcirovic; F.Mumic; S.Bosankic; S.Hasanovic (Archives of Clinical and Biomedical Research, 2020)
The aim of this paper is to highlight the role and level of vitamin D in chronic diseases at the primary level of their treatment. Methods and patients: At Zivinice Health Care Center 81 patients were analyzed between March and September 2019, with 39 men (48.1%) and 42 (51.9%) women. The mean age of the patients was 62 ± 10 years. The youngest patient was 24 years old and the oldest 80 years old. Patients with long-term hypertension (71 patients, 36 women and 35 men), coronary heart disease (16 patients, 8 women and 8 men), type 2 diabetes (T2DM, 45 patients, 22 women and 23 men) were observed, hyperlipoproteinemia (32 patients, 17 women and 15 men), depressive disorder (8 patients, 3 women and 5 men), and anxiety (13 patients, 8 women and 5 men). Vitamin D levels were determined at the University Clinical Center Tuzla, Department of Biochemistry, and 36.8-171.0 mmol / L were taken as reference values. The statistics were analyzed in the SSPS. Results: The mean vitamin D level in patients with chronic diseases was 53.3 mmol / L. Standard deviation (SD) ± 20.9. The reference values for vitamin D levels were 62 patients or 76.5% and 19 or 23.5% had decreased vitamin D. In patients with hypertension, 17 had a reduced vitamin D level (p 0.063). Of the 45 diabetic patients, 13 had reduced levels of vitamin D (p 0.202). Patients with ischemic heart disease 4 of them had lowered vitamin D (p 0.873). In patients with hyperlipoproteinemia, 9 of them have lowered vitamin D (p 0,429). There are 4 patients with reduced levels of vitamin D with depressive disorder and 4 with patients with anxiety disorders with reduced levels of vitamin D (p 0,113). One patient had a body mass index (BMI) of less than 18.5, 6 patients had a neat BMI, 30 patients were overweight. 26 patients had grade I thickness, 16 patients had grade II thickness and two BMI patients over 40 m2 / kg.In t